2022
DOI: 10.3390/nu14020333
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome, Cognitive Impairment and the Role of Diet: A Narrative Review

Abstract: Background: This narrative review presents the association between metabolic syndrome (MetS), along with its components, and cognition-related disorders, as well as the potential reversal role of diet against cognitive impairment by modulating MetS. Methods: An electronic research in Medline (Pubmed) and Scopus was conducted. Results: MetS and cognitive decline share common cardiometabolic pathways as MetS components can trigger cognitive impairment. On the other side, the risk factors for both MetS and cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 174 publications
(189 reference statements)
0
27
0
3
Order By: Relevance
“…On the other hand, it was shown that cognitive impairment is also associated with metabolic syndrome ( 48 ). In fact, CVD and cerebrovascular disease may share underlying mechanisms and risk factors ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was shown that cognitive impairment is also associated with metabolic syndrome ( 48 ). In fact, CVD and cerebrovascular disease may share underlying mechanisms and risk factors ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…43 Dyslipidemia from a high-fat diet can contribute to the development of atherosclerotic plaque, leading to microvascular dysfunction, associated with worse cognitive performance. 44 Higher intake of SFAs was associated with a 15% to 19% increased risk of impairment in memory, psychomotor speed, and cognitive flexibility. 45 Accuracy on both the relational and item tests was better with a low intake of SFAs in children.…”
Section: Lower Dietary Sfas Contribute To Improved Cognition and Redu...mentioning
confidence: 97%
“…Diet plays a critical role in the prevention of metabolic syndromes such as diabetes, cancer, and chronic diseases related with ageing [ 29 , 30 ]. Marine algae-derived bioactive metabolites, such as amino acids, peptides, fatty acids, lipids, carbohydrates, polysaccharides, sterols, polyphenols, photosynthetic pigments, carrageenan, agar, fucoidan, laminaran, naviculan, vitamins, and minerals, exert a persuasive antioxidant activity that has a beneficial effect in fighting the aforementioned diseases [ 5 ].…”
Section: Diversity Of Bioactive Metabolites and Their Potential Healt...mentioning
confidence: 99%